The Prevalence and Correlates of HIV and Undiagnosed Infection among Men Who Have Sex with Men in Hanoi, Vietnam: Findings from a Cross-sectional, Biobehavioral Study - Vu, Nga Thi Thu; Holt, Martin; Phan, Huong Thi Thu; La, Lan Thi; Tran, Gioi Minh; Doan, Tung Thanh; de Wit, John (Frontiers in Public Health, 2016)
Introduction Men who have sex with men (MSM) are a key population for HIV infection in Vietnam and the use of amphetamine-type-substances (ATS) is prevalent and possibly increasing in this population. The reported analysis examines the association between ATS use before or during sex and HIV infection among MSM in Hanoi, Vietnam. Methods This cross-sectional study of 210 MSM was conducted in Hanoi, Vietnam in late 2014. Men tested for HIV and answered questions about demographic characteristics, sexual sensation-seeking, depression, belief in HIV prevention strategies, homosexuality-related stigma and discrimination, recent accessing to HIV prevention services, sexual behaviours and ATS and other drug use behaviours. We performed logistic regression to assess correlates of HIV infection. Results HIV prevalence was 6.7% (14/210) and 85.7% (12/14) of HIV-positive men were not aware of their HIV status. Of the 210 participants, 10.5%, 2.9% and 3.8% of men had used methamphetamine, amphetamine and ecstasy before or during sex in the last three months. In multivariablee analysis, HIV infection was associated with recent sex-related methamphetamine use (adjusted odds ratio (AOR): 5.03; 95% confidence interval (CI): 1.35-18.68); engaging in recent sex work (AOR: 3.55; 95% CI: 1.07-11.75) and homosexuality-related perceived stigma (AOR: 2.32, 95% CI: 0.98-5.47). Conclusion Findings underscore the importance of integrating methamphetamine use interventions into HIV prevention services and scaling-up of gay-friendly, non-stigmatizing HIV testing services for MSM in Hanoi. We recommend the routine assessment of ATS use and undiagnosed infection in this population.